Green synthesis of highly fluorescent AuNCs with red emission and their special sensing behavior for Al3+. Issue 23 (17th February 2016) - Li, Dan; Chen, Zhenhua; Yang, Tiezhu; Wang, Hao; Lu, Nan; Mei, Xifan
Abstract : Facile methods were fabricated for preparation of highly fluorescent AuNCs with red emission usingl -cysteine. Abstract : Facile methods were fabricated for preparation of highly fluorescent AuNCs with red emission usingl -cysteine. Water soluble and aggregation induced AuNCs have been prepared by the employment of the same ligand. The emission wavelength of the as-prepared water soluble AuNCs can be tuned by simply adjusting the amounts of the reactants. Interestingly, it is further found that the fluorescence of AuNCs which has been quenched by Pb 2+ can be recovered by Al 3+ . This provides a new approach for 'turn-on' detection of Al 3+ in aqueous solution. A mechanism for sensing that is related to the residual reducing reagent (THPC) has been proposed base on the investigation of various related nanoclusters-based systems.